(untitled) (International Journal of Engineering and Computer Science, 2017)
In various domains of engineering image processing is being used widely. In the manufacturing industry for example manufacturing of finished products like wooden furniture and other finished products, human eyes are required to check the quality and standard of the finished product. We have proposed a system in which the quality of finished products is monitored by the image processing system. We have used various features of image processing system like morphological operations and image segmentation process to analyze the product images and raise an alarm for the particular product if some defect is found in the finished quality of the product. For example in a paint shop where different panels of the cars are being painted, it is very difficult for the human eyes to find any discrepancy in the quality and texture of painted panels. Hence, an image processing system can be used to find any kind of discrepancy in an efficient manner. Our proposed work will help in optimizing the conventional methods of quality assurance for various products and will also help in cutting down the cost of human resource for a manufacturing plant that manually check the quality and standard of products. We will de developing and implementing the system in real time and will use the MATLAB software for the development of proposed software.